Protection of Kasongan Durian Genetic Resources through Geographical Indications: A Normative Juridical Study of Implementation and Challenges - Nathanael, Faith; Ali, Nuraliah; Wulandari, Vicka Prama (Jurnal Locus Penelitian dan Pengabdian, 2025)
Kasongan durian is a local genetic resource unique to Central Kalimantan, possessing high economic and ecological value but facing threats of exploitation and genetic degradation. This study aims to analyze the role of Geographical Indications (GI) as a legal protection instrument and to identify implementation challenges. The research employs a normative juridical approach, examining legislation, policy documents, and relevant literature. The findings demonstrate that successful GI implementation correlates with institutional strengthening initiatives, showing a 45% improvement in registration success rates when accompanied by capacity-building programs. The results indicate that GI holds strategic legal significance in protecting local genetic resources, recognizing communal rights, and preventing biopiracy. However, implementation faces several challenges, including disputes over genetic resource rights involving traditional knowledge, weak coordination between central and regional governments, administrative complexity in the registration process, and limited human resources and infrastructure. The practical implications include recommendations for establishing district-level Geographical Indications (GI) management bodies with dedicated budgets of IDR 500–750 million annually, developing standardized operating procedures that reduce registration time by 40%, and implementing participatory monitoring systems engaging 80% of local farmers to ensure sustainable protection and economic empowerment through premium pricing mechanisms, potentially increasing farmers’ income by 35–50%. The study concludes by emphasizing the need for institutional capacity building, legal socialization, and multi-stakeholder collaboration to ensure sustainable protection.